2017
DOI: 10.1002/aelm.201700298
|View full text |Cite
|
Sign up to set email alerts
|

High‐Mobility Transparent p‐Type CuI Semiconducting Layers Fabricated on Flexible Plastic Sheets: Toward Flexible Transparent Electronics

Abstract: Transparent p‐type CuI layers with high hole mobility can be fabricated on flexible plastic sheets, a system which has been unattainable with p‐type transparent oxide semiconductors. Mildly heat‐treated CuI layers have mobilities of ≈20 cm2 V−1 s−1, which are comparable to those of p‐type GaN epilayers. Highly transparent p–n diodes with sufficient rectification ratio (106) can be manufactured by employing a heterojunction of p‐type CuI and amorphous n‐type In‐Ga‐Zn‐O layers on plastic sheets. Thus, CuI can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 37 publications
(61 reference statements)
5
85
0
2
Order By: Relevance
“…More importantly, CuI has much higher hole mobility (43.9 cm 2 V −1 s −1 in bulk material) compared with CuSCN and other p‐type oxide semiconductors due to smaller effective hole mass ( m h = 0.3 m 0 , where m 0 is the free electron mass) . This m h is ≈1 order of magnitude smaller than that of CuMO 2 ( m h = 2.6 m 0 ) and is close to the effective electron mass of In 2 O 3 (see Table S1 in the Supporting Information) …”
Section: Basic Parameters Of Tfts Fabricated Under Various Conditionsmentioning
confidence: 71%
“…More importantly, CuI has much higher hole mobility (43.9 cm 2 V −1 s −1 in bulk material) compared with CuSCN and other p‐type oxide semiconductors due to smaller effective hole mass ( m h = 0.3 m 0 , where m 0 is the free electron mass) . This m h is ≈1 order of magnitude smaller than that of CuMO 2 ( m h = 2.6 m 0 ) and is close to the effective electron mass of In 2 O 3 (see Table S1 in the Supporting Information) …”
Section: Basic Parameters Of Tfts Fabricated Under Various Conditionsmentioning
confidence: 71%
“…However, the authors justify this change in conductivity based on iodide diffusion. Yamada et al, 7 observed simultaneously a decrease in charge carrier density (h) and an increase in mobility (m) with increasing temperature. The authors justify CuI lattices to become stoichiometric as a result of the out-diffusion of copper vacancies during heat treatment.…”
Section: A Transparent and Exible Thermoelectric Generatormentioning
confidence: 99%
“…The fact that a maximum Seebeck coefficient of 250 mV K À1 and a hole concentration up to 10 20 cm À3 can be theoretically predicted based on rst-principle calculations, 6 means that currently studies no longer focus on the novelty of the CuI material, but rather on applying it to current technology. Whether applied to rectication layers in solar cells 7 or in p-n thermoelectric modules, 5 the current trend in transparent technology is towards materials that are simultaneously transparent in the visible range of the spectrum and offer some degree of bending exibility. 8,9 In this study, the rst highly transparent and exible p-n thermoelectric generator (TEG) of 17 p-n modules electrically connected in series and thermally in parallel was successfully constructed and tested at temperature gradients of up to 30 C.…”
Section: Introductionmentioning
confidence: 99%
“…50 Vapor iodination is one of the most common strategies for CuI thin-film synthesis, in addition to thermal evaporation. [51][52][53] The next most popular method is some variation of solution-coated synthesis, such as chemical bath deposition (CBD), 54 spin-coating, 55,56 or other similar strategies. 57 Vacuum deposition methods have been used, including pulsed-laser deposition 39,40,[58][59][60][61][62] and reactive sputtering in iodine vapor, 63,64 but these techniques have received considerably less attention.…”
Section: Copper Iodidementioning
confidence: 99%
“…Air and moisture stability of is a well-documented issue, 51,129 due at least in part to the low migration energy barrier for Cu, especially at temperatures above 200°C. [130][131][132] Another problem relevant to its application as a transparent conductor is high surface roughness when synthesized using the common method of vapor iodination of Cu films or by PLD, 52,58,121 which reduces the transparency significantly. However, thermal evaporation 133,134 and sputtering techniques 63,64 do successfully address the surface roughness problem, in addition to vapor iodination using a compound precursor film, such as Cu 3 N or Cu 2 S. 52,135 Despite these challenges, CuI is one of the most widely studied DVMs in the literature today, owing to a few factors, one important factor being the ease with which the material can be synthesized in phase-pure form.…”
Section: Copper Iodidementioning
confidence: 99%